Switching control design for LTI system with uncertain equilibrium: Application to parallel interconnection of DC/DC converters. (November 2022) - Ndoye, Aboubacar; Delpoux, Romain; Trégouët, Jean-François; Lin-Shi, Xuefang
Abstract: This paper addresses the problem of designing a robust control law for uncertain switched affine systems. In order to cope with model uncertainties, a dynamic controller is introduced. Local asymptotic stability of the closed-loop system as well as zero steady state error on the controlled output are proven. A constructive method based on LMI conditions is given. It delivers the control parameters and an estimation of the robust domain of attraction. The proposed strategy is applied on a parallel interconnection of m DC/DC converters. For this system, an extensive discussion is offered on specific difficulties about ill-conditioned matrix inequalities. Finally, by using a user-programmable Field-Programmable Gate Array (FPGA), experimental results are provided to illustrate the effectiveness of the control.